(untitled) (Coffee Science - ISSN 1984-3909)
The progress of rust on coffee trees in organic and conventional crop systems was assessed in two neighboring coffee plantations, in Santo Antônio do Amparo, Minas Gerais state, between December/2004 and October/2006. The plantations were under similar climate, soil and relief conditions. The coffee plants (Coffea arabica L.) evaluated were of the cv. Acaiá MG-474-19, and were eight years old at the beginning of the trial. Comparatively, the progress of the rust in the organic system was not significantly different from the progress in the conventional system. A maximum rust incidence of 24.88% was observed in August/2005, and of 25.72% in August/2006 in the conventional system, and similar incidence values were observed also in the organic. The yield of the organic coffees, in comparison with the conventional ones, was lower in the two years assessed. Comparing the data from 2005 and 2006, it was observed that production decreased by 19.88% in the conventional system and by 5.08% in the organic. This suggests a lower effect of the disease on the following crop of the trees cultivated in the organic system, in relation to those cultivated in the conventional.